Pola Jaringan Komunikasi Internal Pemerintah Kota Denpasar dalam Mengelola Program PRO Denpasar+ - Indah Widia Sari, Ni Luh Ketut; Pascarani, Ni Nyoman Dewi; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2017)
PRO Denpasar+ is one of Denpasar government program since 2013 that consider to public services function. There are 40 government agencies, 4 districs, 43 village level and others agencies in the internal Denpasar City using this program. The aim of this research is to determine the internal communication network of Denpasar city in managing PRO Denpasar+ program. The result of this research shows that the internal communication network used by the government of Denpasar City in managing PRO Denpasar+ program establishes four clicks that describe the tendency of interaction conducted by members of the organization, both between superior and subordinate, and among members who have the same level in the office.   Keywords: Denpasar City Government, Internal Network Communication Pattern , PRO Denpasar+ program